Intelligent Safety: Revolutionizing Home Security with AI and IoT - Jyoti Bolannavar; Divyashree R; Dr. Sumati Ramakrishna Gowda (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The integration of Artificial Intelligence (AI) and the Internet of Things (IoT) has revolutionized home security systems, addressing modern security challenges by providing intelligent, adaptive, and real-time measures. Unlike traditional systems that rely on passive sensors and manual intervention, AI-powered IoT systems leverage advanced machine learning algorithms and interconnected smart devices to predict, detect, and respond to potential threats autonomously. This integration ensures a proactive approach to security, enabling real-time monitoring, anomaly detection, and seamless communication among devices, which significantly reduces response times and enhances reliability. This article explores the key components, functionalities, benefits, challenges, and future prospects of AI-powered IoT home security systems. Through case studies and technical insights, we highlight how these systems enhance security, improve convenience, and address pressing concerns such as data privacy and interoperability.